Novel treatment approaches and future perspectives in follicular lymphoma. (January 2019) - Sutamtewagul, Grerk; Link, Brian K.
Follicular lymphoma (FL) is a common B-cell malignancy characterized by relatively indolent growth and incurability with an expected lifetime course of serial intermittent treatment courses. Many patients with FL have lives shortened by the disease and despite a relatively favorable prognosis relative to other incurable systemic malignancies, optimal management of FL has not been achieved. This review focuses on identifying both patients for whom novel therapies might be most beneficial as well as systematically reviewing novel strategies at various levels of investigation. Prognostic markers incorporating clinical measurements and tumor genetics are discussed, yet at the time of diagnosis do not yet powerfully discriminate patients for whom specific strategies are beneficial. Reassessment of prognosis after evaluating the response to initial therapy is the most powerful identifier of those in need of novel management strategies. For initial therapy of high burden systemic disease, anti-CD20 antibody along with chemotherapy or immunomodulators all offer relatively similar effects on overall survival with subtly different effects on progression-free survival and quality of life. Several new agents currently under investigation in the upfront setting are discussed. Perhaps the best testing ground for novel therapies is in patients with early relapse following initial immunochemotherapy. Ongoing research in multiple therapy classes including, novel monoclonal antibodies, antibody drug conjugates, immunomodulatory agents, intracellular pathway inhibitors, immune checkpoint inhibitors, and epigenetic regulators are discussed herein.